PELAGRA: ASPECTOS CLINICOS E LABORATORIAIS - Vannucchi, H.; Campana, A. O. (My University, 1974)
Clinical and biochemical data were assessed in 14 subjects with pellagra. All had bilateral and symmetrical dermatitis. The principal clinical findings were diarrhea, mental changes, liver enlargement and polyneuropathy. All the patients were addicted to alcohol. Liver biopsy showed steatosis in 10 patients and Laennec's cirrhosis in 2 patients. In 4 cases, the intestinal biopsies showed mild inflammation with shortening and thickening of the villi. Subnormal absorption of xylose was detected in one of 8 patients. High blood pressure was observed in 13 patients.
Pellagra: clinical and biochemical data